Prevalence and socio-demographic factors associated with anaemia in pregnancy in a primary health centre in Rivers State, Nigeria - Geraldine U. Ndukwu; Paul O. Dienye (AOSIS, 2012)
Background: Anaemia, though a common problem in Nigeria, has not been adequately studied amongst pregnant women in primary health care facilities. Objective: This study is aimed at determining the prevalence of anaemia and sociodemographic factors associated with anaemia in pregnancy in a primary health centre in Rivers State, Nigeria. Methodology: This is a cross-sectional study carried out in a primary health centre. Association between variables was analysed using the Chi-square test. Results: Two hundred and twenty-seven pregnant women whose ages ranged from 16 to 40 years with a mean age of 26.8 ± 4.3 years were recruited for the study. The haemoglobin concentration ranged from 6 g/dL - 15 g/dL with a mean of 10.10 ± 1.27g/dL. A total of 142 (62.6%) participants were anaemic. Anaemia was observed to be least prevalent in women within the extremes of reproductive age (≤ 20 years and 36-40 years). There was no statistically significant association between age, educational level and marital status (p > 0.05). The association of anaemia with social class was statistically significant (p = 0.000). Severe anaemia was not a common finding amongst the patients but it was significantly associated with educational status (p = 0.02) and socio-economic status (p = 0.03). Conclusion: The prevalence of anaemia amongst the pregnant participants in the primary health centre was high. Out of all the socio-demographic characteristics, only socio-economic status was significantly associated with anaemia. It is recommended that the socio-economic status of women should be enhanced in line with the Millennium Development Goals to prevent anaemia and to enhance pregnancy outcomes.